2021
DOI: 10.1021/acs.joc.1c00231
|View full text |Cite
|
Sign up to set email alerts
|

Arene Amination Instead of Fluorination: Substitution Pattern Governs the Reactivity of Dialkoxybenzenes with Selectfluor

Abstract: Arene substitution patterns are well-known to affect the regioselectivity of a given transformation but not necessarily the type of reactivity. Herein, we report that the substitution pattern of alkoxyarenes dictates whether a putative one-electron or two-electron reaction predominates in reactions with Selectfluor. A series of amination products is presented, resulting from the single-electron oxidation of electron-rich arenes followed by direct C−H to C−N bond formation. We demonstrate the ability of this tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…31,32 Furthermore, a recent report by Lectka discussed the effect of dialkoxy arene substitution patterns on the reaction pathway upon treatment with Selectfluor; 1,2-and 1,4-substitution favored amination via initial SET, while 1,3-substition gave predominantly the expected electrophilic fluorination. 33 Thus, to begin, we benchmarked the reactivity of in situ Py-HVI (5) against anisole and all three regioisomers of dimethoxybenzene and found that both electronics and substitution pattern played a significant role in determining the reaction outcome (Scheme 2). Under our conditions, anisole gave quantitative conversion to a ∼1:1 ratio of both ortho and para pyridinium salts to diaryliodonium.…”
mentioning
confidence: 99%
“…31,32 Furthermore, a recent report by Lectka discussed the effect of dialkoxy arene substitution patterns on the reaction pathway upon treatment with Selectfluor; 1,2-and 1,4-substitution favored amination via initial SET, while 1,3-substition gave predominantly the expected electrophilic fluorination. 33 Thus, to begin, we benchmarked the reactivity of in situ Py-HVI (5) against anisole and all three regioisomers of dimethoxybenzene and found that both electronics and substitution pattern played a significant role in determining the reaction outcome (Scheme 2). Under our conditions, anisole gave quantitative conversion to a ∼1:1 ratio of both ortho and para pyridinium salts to diaryliodonium.…”
mentioning
confidence: 99%
“…However, the use of À OMe substituent afforded diminished yield (Scheme 2, product 2 c), presumably because Selectfluor may have caused oxidation of the electron rich aryl ring as a side-reaction. [21] A survey of sulphonyl groups revealed that the phenylsulphonyl and tosyl derivatives afforded products in good yields (80 and 88 % respectively) but the nosyl group led to a slight decrease in the yield (Scheme 2, products 2 g-2 i). At this stage, we explored the effect of replacing the aryl ring with a methyl group (R 4 substituent) and observed that yields were significantly reduced (Scheme 2, products 2 j and 2 k).…”
Section: Resultsmentioning
confidence: 99%
“…The first set of precursors explored various electronically distinct substituents on the aryl ring (Scheme 2, products 2 a – 2 f ) and it was observed that the yields were generally high for alkyl and halogen substituents. However, the use of −OMe substituent afforded diminished yield (Scheme 2, product 2 c ), presumably because Selectfluor may have caused oxidation of the electron rich aryl ring as a side‐reaction [21] . A survey of sulphonyl groups revealed that the phenylsulphonyl and tosyl derivatives afforded products in good yields (80 and 88 % respectively) but the nosyl group led to a slight decrease in the yield (Scheme 2, products 2 g – 2 i ).…”
Section: Resultsmentioning
confidence: 99%
“…29 Furthermore, a recent report by Lectka discussed the effect of dialkoxy arene substitution patterns on reaction pathway when treated with Selectfluor; 1,2-and 1,4substitution favored amination via initial SET, while 1,3substition gave predominantly the expected electrophilic fluorination. 30 Thus to begin, we benchmarked the reactivity of in situ Py-HVI (5) against anisole, and all three regioisomers of dimethoxybenzene and found that both electronics and substitution pattern played a significant role in determining reaction outcome (Scheme 2). Under our conditions, anisole gave quantitative conversion to an ~1:1 ratio of both ortho and para pyridinium salts to diaryliodonium.…”
Section: Scheme 1 I(iii) Oxidative Arene Functionalizationsmentioning
confidence: 99%